Análise experimental de vigas constituídas de perfis formados a frio com emendas soldadas submetidas à flexão simples - ALMEIDA, Ariovaldo Fernandes de (2009)
The cold-formed steel sheets have been sufficiently used when it is thought of manufacturing a metallic structure with reduced weight. Its use until some time ago in construction was limited to the secondary structures, but, with considerable growth in research involving this type of material together with development of technical standards, made its use a good solution for certain types of light structures. The present work presents considerations on cold-formed steel sheets, the patened steel, processes of welding and the result of experimental tests with beams with composed section of two profiles U constituted with cold-formed steel sheets, manufactured with two types of patened steel produced in Brazil. In some of these beams, welded sections with coated electrode had been used and were made the comparison with the reference beam, where it was possible to study the influence of the process of welding in the ultimate resistance and the ductility of the beam.